Upper limit on the diffuse flux of ultrahigh energy tau neutrinos from the Pierre Auger Observatory. - Abraham, J; Abreu, P; Aglietta, M; Aguirre, C; Allard, D; Allekotte, I; Allen, J; Allison, P; Alvarez-Muñiz, J; Ambrosio, M; Anchordoqui, L; Andringa, S; et al. (2008)
The surface detector array of the Pierre Auger Observatory is sensitive to Earth-skimming tau neutrinos that interact in Earth's crust. Tau leptons from nu(tau) charged-current interactions can emerge and decay in the atmosphere to produce a nearly horizontal shower with a significant electromagnetic component. The data collected between 1 January 2004 and 31 August 2007 are used to place an upper limit on the diffuse flux of nu(tau) at EeV energies. Assuming an E(nu)(-2) differential energy spectrum the limit set at 90% C.L. is E(nu)(2)dN(nu)(tau)/dE(nu)<1.3 x 10(-7) GeV cm(-2) s(-1) sr(-1) in the energy range 2 x 10(17) eV< E(nu)< 2 x 10(19) eV.